1971
DOI: 10.1677/joe.0.0490243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oestradiol on Cell Proliferation and Histological Changes in the Uterus and Vagina of Mice

Abstract: SUMMARY The duration of the phase of DNA synthesis (S-phase) and turnover times were measured by autoradiography in the vaginal and endo-uterine epithelium of spayed mice at different times after a single oestradiol injection. With three doses of oestradiol (0·3, 1·2 and 10·0 μg), changes of turnover time followed similar patterns in uterine epithelium, but maximal activation and subsequent levelling off of proliferation rates were reached sooner with higher doses. In the vagina, no significant dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

1973
1973
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 0 publications
4
51
0
1
Order By: Relevance
“…In a preliminary study, we also found that BPA induced expression of c-jun in both strains of rats, with steadystate levels reaching maximum at 2-3 hr after treatment (data not shown). Likewise, the time-course of the DNA synthetic response in the F344 vagina following a single injection of BPA is similar to that produced by natural estrogens (26,27). In studies on estrogenic effects in non-reproductive tissues, Dodge et al (25) (2).…”
Section: Resultsmentioning
confidence: 92%
“…In a preliminary study, we also found that BPA induced expression of c-jun in both strains of rats, with steadystate levels reaching maximum at 2-3 hr after treatment (data not shown). Likewise, the time-course of the DNA synthetic response in the F344 vagina following a single injection of BPA is similar to that produced by natural estrogens (26,27). In studies on estrogenic effects in non-reproductive tissues, Dodge et al (25) (2).…”
Section: Resultsmentioning
confidence: 92%
“…Oestrogen is known to regulate diverse physiological processes of target tissues including those of the reproductive (Galand et al 1971), cardiovascular (Barrett-Connor & Bush 1991) and skeletal (Migliaccio et al 1992) systems. These tissues have been shown to express oestrogenbinding molecules, namely oestrogen receptors (ER), by studies using various techniques such as binding assays (Eisenfeld 1970, Saiduddin & Milor 1971, Sen & Talwar 1973, autoradiography (Stumpf & Sar 1975), immunohistochemistry (Greene et al 1984), reverse transcriptasepolymerase chain reaction (RT-PCR) (Couse et al 1997 and in situ hybridization (Kuiper et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases of uterine weight and endometrial height, as well as hypertrophy of the luminal epihelium, have been established as reliable indexes of estrogenic effects (Galand et al, 1971;Korach and McLachlan, 1995;Tinwell et al, 2000). The most pronounced uterotrophic effects were observed in the rats treated with E 2 .…”
Section: Discussionmentioning
confidence: 99%